2011
DOI: 10.1002/eat.20807
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole in anorexia nervosa and low‐weight bulimia nervosa: Case reports

Abstract: In summary, these findings support the need to perform controlled trials of aripiprazole in AN and BN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 84 publications
2
40
0
2
Order By: Relevance
“…For instance, stimulants such as methylphenidate or the antidepressant bupropion frequently affect food intake and promote weight loss (Anderson et al, 2002;Goldfield et al, 2007). In AN, small studies using the dopamine D2 antagonist haloperidol or the dopamine D2 partial agonist aripiprazole suggested beneficial effects on core symptoms of AN (Cassano et al, 2003;Trunko et al, 2011). Importantly, the stimulant amphetamine increased, whereas haloperidol decreased brain response in a human temporal difference model paradigm (Menon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, stimulants such as methylphenidate or the antidepressant bupropion frequently affect food intake and promote weight loss (Anderson et al, 2002;Goldfield et al, 2007). In AN, small studies using the dopamine D2 antagonist haloperidol or the dopamine D2 partial agonist aripiprazole suggested beneficial effects on core symptoms of AN (Cassano et al, 2003;Trunko et al, 2011). Importantly, the stimulant amphetamine increased, whereas haloperidol decreased brain response in a human temporal difference model paradigm (Menon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SGAs may help increase insight and willingness to engage in treatment and decrease the negative cognitive processes related to food, body-image, and weight-gain. Previous case studies of adolescents treated with SGAs have shown decreased obsessional thinking, agitation, and body image concerns (McKnight & Park, 2010;Trunko et al, 2011;Flament, et al, 2012;Dennis et al, 2006). In an activity-based anorexia model in mice, olanzapine was found to significantly decrease food-related anticipatory activity, indicating that olanzapine may help reduce anxious behaviors related to AN (Klenotich et al, 2012).…”
Section: Psychological Considerations In Future Sga Researchmentioning
confidence: 90%
“…1-5 mg/d olanzapine, 100-400 mg/d quetiapine) were commonly used. There is also one case report supporting the use of aripipazole in three patients with bulimia nervosa as well as eight with anorexia nervosa (Trunko et al 2010). In this series, the three patients with bulimia nervosa had or previously had low weight.…”
Section: Antipsychotic Medicationsmentioning
confidence: 92%